Does Elderly Employment Reduce Job Opportunities for Youth? - Jasmin, Alyssa Farha (World Bank, Malaysia, 2021)
The aging of populations around the world and the associated fall in the working age population are expected to adversely affect countries’ GDP growth in coming decades. These demographic shifts will also place fiscal pressure on governments, given the need either to finance pension systems or to support the most vulnerable in retirement. Extending working lives is imperative but often politically challenging, due to the widespread belief that extending employment for older workers will limit employment opportunities for youth. Global empirical evidence summarized in this brief, as well as original analysis, does not support this belief, and in fact suggests that elderly employment has positive effects on youth employment, on the well-being of older workers, and on economies and societies. There is much to gain in creating a supportive regulatory environment to harness the economic potential of older workers by eliminating age-biased hiring practices, allowing for flexible working conditions, and providing equal opportunities for upskilling and reskilling.